An Analysis of the Caregiver Archetype in the Film Hacksaw Ridge (2016) - Fascho Bintang Maulana; Winarti; Sri Kuncoro Dibyo Sarjono Maskuri (Universitas Negeri Surabaya, 2026)
Using Jung’s archetypal theory, this study analyzes the Caregiver Archetype in Hacksaw Ridge (2016). While prior research has focused on heroism, faith, and courage, little attention has been given to caregiving traits. Using qualitative textual and content analysis of dialogues, actions, and narrative situations, the study identifies four caregiver characteristics: compassion (empathy and concern), protection (safeguarding the vulnerable), nurturing (physical and emotional care), and selflessness (prioritizing others’ welfare over personal safety). The study aims to identify and analyze the caregiving traits portrayed through the film's characters, actions, and narrative situations. By concentrating specifically on the Caregiver Archetype, this research contributes to the development of Jungian archetypal criticism in film studies and expands our understanding of how values such as compassion, protection, nurturing, generosity, and self-sacrifice are represented in cinematic narratives. The findings of this research show that caregiving acts as a psychological and moral force in the film, even within the context of war. This contributes to Jungian criticism by highlighting the Caregiver Archetype’s role in shaping narrative meaning in war films.